Energy metabolism and obesity stratified by BMI: impact on lipid oxidation, a cross-sectional observational study - de-Medeiros, Lorena; San Martin, Rocío; Junqueira, Gizela; de Oliveira, Joyce; Trunce-Morales, Silvana Trinidad; Nogueira-de-Almeida, Carlos; Marchini, Julio Sérgio (Frontiers in Nutrition, 2025)
IntroductionObesity is a complex disorder of nutritional-metabolic factors, involving, among others, the environment, mental health, and physical activity levels. Biological and social aspects are fundamental to understanding the genesis and progression of obesity. Energy metabolism, particularly resting energy expenditure (REE) and substrate oxidation, plays a key role in maintaining energy balance. REE reflects the energy required to sustain vital functions such as cellular metabolism, organ function, and homeostasis. Variations in body mass index (BMI) are associated with differences in REE and substrate oxidation, which may contribute to the metabolic predisposition to obesity. Based on this, we hypothesize that in obesity, the energy metabolism is characterized by reduced lipid oxidation.ObjectiveTo explore the relationship between energy metabolism parameters and predisposition to obesity.MethodsAn observational, cross-sectional study was conducted among 216 adult women (≥18 years), non-hospitalized and free of chronic diseases, with different BMI classifications. Between 2017 and 2024, energy metabolism assessments were performed using indirect calorimetry, with direct measurement of oxygen consumption (VO₂) and carbon dioxide production (VCO₂) at rest, and substrate oxidation estimated from respiratory quotient analysis.ResultsWomen with obesity (BMI ≥ 30 kg/m2) showed a significantly higher rate of REE and lipid oxidation compared with women with normal BMI (<25 kg/m2) (p < 0.05). Women with obesity oxidize more lipids than women without obesity (p < 0.05).ConclusionIn adult women, obesity is associated with elevated resting energy expenditure and lipid oxidation, which demonstrated discriminatory value in distinguishing the obese state from non-obese women. These results underscore the relevance of energy metabolism parameters in understanding the metabolic adaptations linked to higher BMI.